2018
DOI: 10.1111/age.12652
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide detection ofCNVs associated with beak deformity in chickens using high‐density 600KSNParrays

Abstract: Beak deformity (crossed beaks) is found in several indigenous chicken breeds including Beijing-You studied here. Birds with deformed beaks have reduced feed intake and poor production performance. Recently, copy number variation (CNV) has been examined in many species and is recognized as a source of genetic variation, especially for disease phenotypes. In this study, to unravel the genetic mechanisms underlying beak deformity, we performed genome-wide CNV detection using Affymetrix chicken high-density 600K d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Moreover, mutations in RET are also associated with the disorders such as multiple endocrine neoplasia, type IIA, multiple endocrine neoplasia, type IIB, Hirschsprung disease, and medullary thyroid carcinoma [ 44 ]. In addition, its interacting gene, LRIG2 , was also identified as one of the most promising candidate genes underlying this trait in our previous CNV study within the same genotyped data used here [ 45 ]. Thus, the RET and LRIG2 genes might jointly contribute to the development of deformed beaks.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mutations in RET are also associated with the disorders such as multiple endocrine neoplasia, type IIA, multiple endocrine neoplasia, type IIB, Hirschsprung disease, and medullary thyroid carcinoma [ 44 ]. In addition, its interacting gene, LRIG2 , was also identified as one of the most promising candidate genes underlying this trait in our previous CNV study within the same genotyped data used here [ 45 ]. Thus, the RET and LRIG2 genes might jointly contribute to the development of deformed beaks.…”
Section: Discussionmentioning
confidence: 99%
“…Following the first two genome-wide scans for CNVs in human genome [7,8], a large number of CNV detection studies have been performed, which revealed that CNVs are ubiquitously distributed in genome and can influence the phenotype via regulations of gene expression and gene dosage [9][10][11]. Besides, numerous studies in other species have also shown that CNVs contributed to phenotypic variation of complex diseases and traits [12][13][14][15][16][17][18][19], including MD in chicken [20][21][22]. Two major traditional platforms employed in CNV detection are based on SNP chips, one is known as comparative genomic hybridization (CGH) array, and the other is SNP genotyping array.…”
Section: Introductionmentioning
confidence: 99%
“…Following the rst two genome-wide scans for CNVs in human genome [7,8], an large number of CNV detection studies have been performed, which revealed that CNVs are ubiquitously distributed in the genome and can in uence the phenotype via regulations of gene expression and gene dosage [9][10][11]. Besides, numerous studies in other species have also shown that CNVs contributed to phenotypic variation of complex diseases and traits [12][13][14][15][16][17][18][19], including MD in chicken [20][21][22]. Two major traditional platforms employed in CNV detection are based on SNP chips, one is known as comparative genomic hybridization (CGH) array, and the other is SNP genotyping array.…”
Section: Introductionmentioning
confidence: 99%